Mouse models, antibodies, and neuroimaging: Current knowledge and future perspectives in neuropsychiatric systemic lupus erythematosus (NPSLE) - Tomalla, Vanessa; Schmeisser, Michael J.; Weinmann-Menke, Julia (Frontiers in Psychiatry, 2023)
As a chronic autoimmune disease systemic lupus erythematosus (SLE) can also affect the central and the peripheral nervous system causing symptoms which are summed up as neuropsychiatric systemic lupus erythematosus (NPSLE). These symptoms are heterogenous including cognitive impairment, seizures, and fatigue, leading to morbidity or even mortality. At present, little is known about the pathophysiological processes involved in NPSLE. This review focuses on the current knowledge of the pathogenesis of NPSLE gained from the investigation of animal models, autoantibodies, and neuroimaging techniques. The antibodies investigated the most are anti-ribosomal P protein antibodies (Anti-rib P) and anti-N-Methyl-D-Aspartic Acid Receptor 2 antibodies (Anti-NR2), which represent a subpopulation of anti-dsDNA autoantibodies. Experimental data demonstrates that Anti-rib P and Anti-NR2 cause different neurological pathologies when applied intravenously (i.v.), intrathecally or intracerebrally in mice. Moreover, the investigation of lupus-prone mice, such as the MRL/MpJ-Faslpr/lpr strain (MRL/lpr) and the New Zealand black/New Zealand white mice (NZB × NZW F1) showed that circulating systemic antibodies cause different neuropsychiatric symptoms compared to intrathecally produced antibodies. Furthermore, neuroimaging techniques including magnetic resonance imaging (MRI) and positron emission tomography (PET) are commonly used tools to investigate structural and functional abnormalities in NPSLE patients. Current research suggests that the pathogenesis of NPSLE is heterogenous, complex and not yet fully understood. However, it demonstrates that further investigation is needed to develop individual therapy in NPSLE.